A Dictionary of Historical Anthroponymy of the Khori-Buryat. Review of the book: Zhamsaranova, R. G., Altaeva, V. I., & Bardakhanova, Z. D. Slovar’ istoricheskoi antroponimii khori-buriat [A Dictionary of Historical Anthroponymy of the Khori-Buryat]. Cheboksary: Sreda, 2022. 332 p. - Svetlana Menkenovna Trofimova; Ervena Vladimirovna Erdnieva (Вопросы ономастики)
This review focuses on The Dictionary of Historical Anthroponymy of the Khori Buryats, which presents a comprehensive collection of personal names from all 14 clans of the Khori Buryats. The dictionary is based on anthroponymic data recorded in the 1830–1831 revision inventories of the Khorinsk and Aginsk Steppe Dumas of Irkutsk Province, as well as on valuable fieldwork materials relevant to historical-comparative and comparative linguistic studies. The volume represents the outcome of many years of onomastic research conducted by the authors in Eastern Transbaikalia. It offers, for the first time, a systematic regional anthroponymic corpus: a multilingual dataset of Buryat personal names. These names are rooted in both Turkic and Mongolic linguistic traditions, shaped by substrate influences, and include a substantial number of Tibetan-Sanskrit elements alongside a smaller proportion of names of Russian origin.